An Autopsy-Based Study for Estimation of Stature From Anthropometry of Percutaneous Length of Femur in Male Population of Central India Region (M.P.) - Shrivastava, Mohit; Thakur, P S; Singh, B K; Kumar Vishwakarma, Ashish (Journal of Forensic Medicine and Toxicology, 2025)
Estimation of stature holds a special attention in the field of forensic medicine & forensic anthropology. Among the  various parameters of identification, individual’s stature is an inherent characteristic. It becomes very difficult to predict  the physical identity of an individual when only mutilated and dismembered remains of dead body are brought for post  mortem examination. The aim of the present study was to find the correlation between anthropometry of percutaneous  length of femur and stature in males and to derive a regression equation formula and multiplication factor to estimate the  stature from percutaneous length of femur anthropometry in the Central India region Madhya Pradesh. This cross-sectional study was carried out on 250 deceased males of age between 20-60 years, brought for postmortem examination to  the mortuary of Forensic Medicine Department, M.G.M. Medical College and M.Y. Hospital, Indore (M.P.). The mean  right and left percutaneous femoral length found 39.73 ± 1.613 and 39.74 ± 1.606 cm respectively, whereas the mean  stature was found to be 165.83 ± 7.98 cm. In this study, the maximum stature in males was found to be 185.0 cm and the  minimum stature was found to be 150.0 cm. The correlation between percutaneous femoral length and stature was found  to be positively correlated and the association was highly significant. The multiplication factor for percutaneous femoral length was found to be 4.17. Multiplication factors become  essential in cases of forensic analysis when only limb or fragmented body part with soft tissue is available for analysis
Keywords: Identification; Anthropometry; Stature; Percutaneous Femoral Length